Stable oxygen and hydrogen isotopic composition of pore water (δ18O; δD) of sediment core GeoB24343-1 - Matthias Zabel; Martin Kölling; Gerhard Bohrmann; Nele Behrendt (PANGAEA, 2023)
The samples are retrieved from sediment core GeoB24343-1 (Monza MV; 0-318 cm) in the Olimpi mud volcano field, located south of Crete at the Mediterranean Ridge accretionary complex. Hydrogen (δD) and oxygen (δ18O) isotopes were analysed in the sediment geochemistry laboratory at MARUM using a Picarro 2130i CRD System. Approximately 2 mL of the onboard extracted pore water was used per measurement. The results are an average of at least three injections, while a total of 9 injections of 7 μL each have been analysed per sample. Results are reported in delta notation ( extperthousand) relative to V-SMOW2 -SLAP2 with nominal standard (std) deviation of 0.03 for δ18O and 0.3 for δD. Actual std deviation is between 0.02 and 0.29 for δ18O and between 0.04 and 1.68 for δD.